Impact of transformational leadership on nurse work outcomes. (26th July 2016) - Brewer, Carol S.; Kovner, Christine T.; Djukic, Maja; Fatehi, Farida; Greene, William; Chacko, Thomas P.; Yang, Yulin
Abstract: Aims: To examine the effect of transformational leadership on early career nurses' intent to stay, job satisfaction and organizational commitment. Background: Lack of leadership support is one of the top reasons staff nurses leave. Current studies reported mixed results about the impact of transformational leadership on key nurse outcomes. However, little is known whether leadership directly or indirectly affects satisfaction, organizational commitment and intent to stay. Design: This study was a cross‐sectional study of nurses who had been licensed for 7·5‐8·5 years which was part of a 10‐year longitudinal panel design. Methods: The analytic sample was 1037 nationally representative newly licensed Registered Nurses. Data were collected from January–March 2013. We used a probit model to model the relationship between transformational leadership and intent to stay, organizational commitment and job satisfaction. Results: Transformational leadership did not have a significant impact on intent to stay and job satisfaction, but significantly associated with organizational commitment. Organizational commitment, job satisfaction, mentor support, promotional opportunities and age were positively associated with intent to stay, while ethnicity, non‐local job opportunities and work settings were negatively associated with intent to stay. Conclusions: Transformational leadership had no direct relationship with intent to stay and job satisfaction and had a small direct positive effect on organizational commitment. Transformational leadership has potential to slow attrition and retain nurses by creating a positive work environment that supports nurses. Any improvement in job satisfaction and organizational commitment would positively increase the change in probability for intent to stay.